2022
DOI: 10.1039/d1fo04224f
|View full text |Cite
|
Sign up to set email alerts
|

Co-interventions withClostridium butyricumand soluble dietary fiber targeting the gut microbiota improve MAFLDviathe Acly/Nrf2/NF-κB signaling pathway

Abstract: Purpose: The pathogenesis of metabolic associated fatty liver disease (MAFLD) is complex. The lipid metabolic disorder, chronic inflammation, and oxidative stress are the core events for MAFLD. Dietary intervention is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…Second, epidemiological study showed that acrylamide exposure was positively associated with systemic in ammatory mediator plasma C-reactive protein. Animal experiments demonstrated that dietary ber mediated oxidation by activating the Acly/Nrf2/NF-κB signaling pathway, which exerted antiin ammatory effects by inhibiting the differentiation of macrophages into pro-in ammatory M1 macrophages (Shao et al 2022). Thus, it is plausible to consider that the pathogenesis of dietary ber may be related to decreased concentrations of AA hemoglobin biomarkers's through its anti-in ammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Second, epidemiological study showed that acrylamide exposure was positively associated with systemic in ammatory mediator plasma C-reactive protein. Animal experiments demonstrated that dietary ber mediated oxidation by activating the Acly/Nrf2/NF-κB signaling pathway, which exerted antiin ammatory effects by inhibiting the differentiation of macrophages into pro-in ammatory M1 macrophages (Shao et al 2022). Thus, it is plausible to consider that the pathogenesis of dietary ber may be related to decreased concentrations of AA hemoglobin biomarkers's through its anti-in ammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the effects of perillartine on fat accumulation in vivo, mice were fed a normal diet or a high-fat diet supplemented with perillartine, with normal and high-fat diets serving as controls. [25][26][27] Compared with the high-fat diet, which showed rapid weight gain, the addition of perillartine could slow down the rate of weight gain in a dose-dependent manner, and there was a significant difference in body weight between the groups after 6 weeks of the high-fat diet. However, no difference in body weight was observed between the three groups given the normal diet (Fig.…”
Section: Perillartine Reduces High-fat Diet-induced Lipid Deposition ...mentioning
confidence: 99%
“…The microbial metabolite, indole-3-acetic acid (I3A), which is elevated after sleeve gastrostomy, was found to promote M2 differentiation both in vivo and in vitro , relieving obesity-associated NAFLD ( Wang Y. et al, 2021 ). Further, coadministration of Clostridium butyricum and soluble dietary fiber reduced the percentage of KCs and the activation of M1 macrophages in liver by suppressing the TLR4/NF-κB signaling ( Shao et al, 2022 ).…”
Section: Hepatic Macrophages As Microbial Regulating Targets In Infla...mentioning
confidence: 99%
“…In general, KCs are responsible for sensing and processing biochemical signals, such as pathogen components, cell fragments, and endo/exogenous metabolites (Diehl et al, 2020;Li W. et al, 2022). They can trigger primary inflammation and secrete chemokines to recruit MoMφs for further inflammatory responses (Wen et al, 2021;Zhou J. et al, 2022). Hepatic macrophages can also regulate inflammatory responses when stimulated with anti-inflammatory factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation